Estudio jurídico-comparativo respecto a la tenencia de armas traumáticas y su incidencia en el fenómeno criminal en la legislación ecuatoriana - Rodríguez Jumbo, Jorge Alexander (2023)
The present curricular research work entitled "Legal-comparative study regarding the tenure of traumatic weapons and its incidence in the criminal phenomena in ecuadorian legislation", arises from the fact that citizen insecurity is one of the most worrying problems in our country, and measures must be taken to curb the delinquent index. In recent years, there has been a substantial increase in armed robberies, assaults, and intimidation on the streets, and it is fascinating to see how criminals intimidate citizens who wish to live in an environment of peace and serenity that is intended to be guaranteed by our Ecuadorian laws. Therefore, through the study and research carried out, it became evident that in our country the problem of traumatic weapons is a topic that is little known by citizens and even by the authorities who have done little or nothing to control their commercialization, possession or carrying. The problem arises because this type of non-lethal weapon can be acquired very easily through digital markets and even physical stores without considering that they are mostly used for crimes, since the mere fact of having them already constitutes a dangerous crime. It is because of this situation that it has been proposed to include traumatic weapons in the law on weapons, ammunition, explosives and accessories within a catalog where they are differentiated from lethal weapons and to consider their possession as a contravention, in addition to their use being controlled and regulated by the competent entity in the same way that lethal weapons are regulated. For the purpose of developing the relevant aspects of this work, different research parameters were established, such as doctrinal, legal and conceptual ones. The type of research was mainly bibliographic. Furthermore, the necessary methods needed to be applied, such as scientific, inductive, deductive, analytical, exegetical, hermeneutic, maieutic, comparative, statistical, and synthesized methods. And with respect to the survey, techniques such as surveys and interviews were applied, which made it possible to obtain the criteria of professionals and specialists in criminal law, thereby verifying the problem and suggesting the inclusion of traumatic weapons and differentiating them within the law concerning weapons, ammunition, explosives, and accessories, as well as punishing their possession as a violation.